Economic Empowerment of Gelgel Indigenous Village Communities Due to the Impact of Covid-19 Through Village Credit Institutions - AAA. Ngr. Sri Rahayu Gorda; Ketut Elly Sutrisni; Ida Ayu Oka Martini (Fakultas Hukum, Universitas Warmadewa, 2022)
Since then, the government has taken a number of steps to mitigate the impact of the Covid-19 epidemic in a number of industries. Restrictions on community activities affect business activities which in turn have an impact on the economy in the employment sector. To overcome the impact of the Covid-19 pandemic, assistance was held for the Gelgel Indigenous Village community in order to help the community's economy in order to meet the needs of their family life. The assistance provided in this activity is to obtain cheap credit bailouts from the Gelgel Village Traditional Village Financial Institution (LPD) in the Klungkung Regency and District by providing loan capital for workers who have been dismissed due to the closure of the company where they work. work. This activity aims to help the Gelgel Traditional Village community in their economic sustainability. The method used is the method of analyzing the community situation. The results show that of the three indicators, namely interpersonal roles, information-related roles, decision-making roles, it can run well.